2020
DOI: 10.1038/s41598-020-60607-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress, cognitive decline and the development of dementia in amnestic mild cognitive impairment

Abstract: to determine the relationship between psychological stress with cognitive outcomes in a multi-centre longitudinal study of people with amnestic mild cognitive impairment (aMci) we assessed three parameters of psychological stress (Recent Life changes Questionnaire (RLcQ); the perceived Stress Scale (PSS) and salivary cortisol) and their relationship with rates of cognitive decline over an 18 month follow up period and conversion to dementia over a 5.5 year period. In 133 aMCI and 68 cognitively intact particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
(37 reference statements)
1
23
1
Order By: Relevance
“…The Perceived Stress Scale is one of the most extensively used psychometric tools for measuring the perception of stress in healthy and pathological populations [20][21][22]. It is a measure of the grade to which circumstances in one's life are evaluated as stressful.…”
Section: Perceived Stress Scalementioning
confidence: 99%
“…The Perceived Stress Scale is one of the most extensively used psychometric tools for measuring the perception of stress in healthy and pathological populations [20][21][22]. It is a measure of the grade to which circumstances in one's life are evaluated as stressful.…”
Section: Perceived Stress Scalementioning
confidence: 99%
“…While our findings suggest that psychological distress may increase the risk of cognitive impairment, the opposite pathway is also possible, that is, worse memory and executive function may cause psychological distress. For instance, individuals with cognitive impairment have shown to be at a higher risk for anxiety and depressive disorders later in life (Chen, Ganguli, Mulsant, & DeKosky, 1999; Mirza et al., 2017; Petkus, Reynolds, Wetherell, Kremen, & Gatz et al., 2017; Sussams et al., 2020). This phenomenon could reflect ongoing brain disease, a psychological reaction of individuals to their awareness of their cognitive decline or both.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the aforementioned assumptions, the desired total sample size was 80. Considering that comparable studies for dementia cohorts with a sample size > 100 showed efficacy in describing neuropsychiatric phenomena, we contacted 150 patients and 150 caregivers (26)(27)(28).…”
Section: Design Of the Ongoing Studymentioning
confidence: 99%